2013
DOI: 10.1016/j.exppara.2013.04.006
|View full text |Cite
|
Sign up to set email alerts
|

A new approach to characterization of the resistance of populations of Rhipicephalus microplus (Acari: Ixodidae) to organophosphate and pyrethroid in the state of Minas Gerais, Brazil

Abstract: h i g h l i g h t sOf the 587 populations tested for pyrethroids, 97.44% were resistant. For organophosphates were tested 306 populations and 75.49% were resistant. Into populations resistant to pyrethroids, 91% are heterozygous. The analysis confirmed the serious problem of resistance of Rhipicephalus microplus populations. g r a p h i c a l a b s t r a c t a b s t r a c tThe monitoring of resistance of cattle tick populations in Brazil to the chemical bases in use is largely limited to investigation of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
2
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 13 publications
1
20
2
3
Order By: Relevance
“…However, more than half (65%) of the farmers considered that they were satisfied with their tick control. Given the increasing resistance of ticks to commercial products (DAHER et al, 2012;UENO et al, 2012;MENDES et al, 2011;FAZA et al, 2013), the fact that most of these farmers were satisfied with their tick control must have been due to the crossbreeding of their herds (European x Zebu), which was present on 82.5% of the farms (Table 2). Bertolucci (2010) also found that more than half (58.8%) of the dairy producers in the south of the State of Minas Gerais reported that they were relatively satisfied with their tick control and, in that study too, crossbred cattle formed the majority (73.6%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, more than half (65%) of the farmers considered that they were satisfied with their tick control. Given the increasing resistance of ticks to commercial products (DAHER et al, 2012;UENO et al, 2012;MENDES et al, 2011;FAZA et al, 2013), the fact that most of these farmers were satisfied with their tick control must have been due to the crossbreeding of their herds (European x Zebu), which was present on 82.5% of the farms (Table 2). Bertolucci (2010) also found that more than half (58.8%) of the dairy producers in the south of the State of Minas Gerais reported that they were relatively satisfied with their tick control and, in that study too, crossbred cattle formed the majority (73.6%).…”
Section: Discussionmentioning
confidence: 99%
“…(B.) microplus (FAZA et al, 2013;BRITO et al, 2015). In the survey by Amaral et al (2011b) in the State of Minas Gerais, use of alternative control methods such as homeopathy was cited by 3.1%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rhipicephalus (Boophilus) microplus is considered the most important ectoparasite in the cattle industry because of the direct and indirect damage that it can cause to animal health, which considerably limits bovine productivity (Calligaris et al, 2013;Maza et al, 2013). It has a wide geographic distribution, spanning tropical and subtropical regions between parallels 32 • N latitude and 35 • S latitude, including countries in Latin America, Africa, Asia and Oceania (Wharton et al, 1970).…”
Section: Introductionmentioning
confidence: 99%
“…Rhipicephalus (Boophilus) microplus is considered to be the most important ectoparasite in cattle industry because of the direct and indirect damage it can cause to animal health, thereby considerably limiting bovine productivity (CALLIGARIS et al, 2013;FAZA et al, 2013). It possesses a wide geographical distribution, encompassing tropical and subtropical regions situated between the parallels 32° latitude north and 35° latitude south, comprising countries in Latin America, Africa, Asia and Oceania (WHARTON, 1974).…”
Section: Introductionmentioning
confidence: 99%